Highlights on the phenomena of Sbeia ground collapse, preliminary diagnosis from field observations - abouessa, ashour; Giuma Swei, Giuma Swei (Sharwes Scientific Journal, 2026)
Ground cracks and collapse occurred recently in Awlad Abu Aisha area, municipality of Sbeia, is a serious event as it is unexpectedly caused abnormally extensive damage to the ground. In general, ground cracking is regarded as a natural phenomenon that are usually derived by seasonal temperature fluctuations acted on recent sediments dominated by mud; muddy soil. Such soil owns property preferable for shrinkage cracks to occur. The affected site is a low-populated agricultural region with no heavy building nor industrial activities. While the habitually known ground cracks are small and not dangerous, these ones, called Sbeia cracks, appear to have been unusually rapidly enlarged. They become a source of wariness to the local inhabitants who considered these cracks as a mysterious phenomenon. Apart from the public opinions about the secret behind these cracks, there is no any published research devoted to their origin. This is prompted us to visit/revisit the site of ground damage intending to investigate all aspects and appearances related to the Sbeia cracks. Consequently, the visible field features related to this phenomenon are then analysed in relation to the ambient geological and climatic circumstances. Observations are then discussed in the light of elsewhere documented researches. Although our study lies exclusively on visual observations, it comes up with reasonable explanation concerning the causes behind this ground damage. The study concluded that this feature is emerged as a result of the interaction of the properties of the soil with the local geo-climatic conditions.